Scheduled optimal sleep duration and screen exposure time promotes cognitive performance and healthy BMI: a study among rural school children of India. Issue 10 (26th November 2021) - Dutta, Koumi; Mukherjee, Ruchira; Das, Rittick; Chowdhury, Abanti; Sen, Devashish; Sahu, Subhashis
ABSTRACT: Unhealthy Body Mass Index (BMI) is a primary manifestation of metabolic disorder. Disruption of sleep is a major factor that has been observed to culminate into metabolic disorders. Sleep parameters are also influenced by the screen exposure duration associated with the use of electronic devices. Screen Exposure Time (SET) also has an effect on metabolism due to sedentary nature of the activity. Both SET and disrupted sleep are related with cognitive performance. Children are affected by sleep disruption and prolonged SET. Efforts to ameliorate in a primordial age may be more effective to reduce their predisposition to unhealthy BMI and detrimental changes of cognitive performance. In order to mitigate the scourge of unhealthy BMI prevalent in developing countries and to improve cognitive performance, it is important to administer proper sleep duration and SET. It is necessary to delineate an optimum duration of sleep and identify the optimum duration of SET in this regard. SET equal to and beyond 2 hours/day lead to increase sleep debt and decline of cognitive performance. Rise in BMI is associated with increase in SET. Sleep duration of 6–7 hours among participants yields better cognitive performance than those with sleep duration below or above 6–7 hours.